Trypsin Inhibitor of Ricinus communis L. (Euphorbiaceae) in the Control of Spodoptera frugiperda (Smith, 1797) (Lepidoptera: Noctuidae) - Ramos, Vinicius O.; Alves, Dejane S.; Carvalho, Geraldo A.; Santos, Custódio D.; Cavalheiro, Alberto J. [UNESP]; Oliveira, Júlia A. C.; Marques, Tamara R.; Simão, Anderson A.; Saczk, Adelir A. (MDPI, 2024)
The fall armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae), is a polyphagous insect of various agricultural crops. The methods used for its control have led to the selection of resistant insect populations, which justifies the search for new alternatives for the management of this insect. Accordingly, in the present study, trypsin inhibitors present in the leaf extract of Ricinus communis (Euphorbiaceae) were investigated for their activity against S. frugiperda. Chemometric optimization methods were developed for the extraction, purification, identification, and structural characterization of the inhibitors. In addition, the effect of R. communis extract on S. frugiperda development was evaluated. Inhibitor extraction was chemometrically optimized, yielding an extract with an antitryptic activity of 94,837.14 mUIT g−1. The R. communis extract was purified and found to contain two compounds (adenosine and ricinine) exhibiting trypsin inhibitor activity. However, after purification, only ricinine inhibited S. frugiperda trypsin in vitro (103.21 mUIT mg−1). The extract was added to the diet of S. frugiperda larvae, resulting in reduced digestion, increased protein in the feces (control = 12,571 μg protein/mg feces; 1818.2 g mL−1 = 16,867 μg protein/mg feces), and insect mortality. At the highest concentration, the treatment led to an LT50 of 15.9 days and a cumulative survival rate of 18.5%. Based on the results of this study, it is possible that ricinine binds to the catalytic site of trypsin, causing the mortality of S. frugiperda larvae.
Keywords: botanical insecticides; enzymatic inhibitor; fall armyworm; secondary metabolites